Kwestionariusze EQ-5D i EQ-VAS jako metody pośredniego pomiaru jakości stanu zdrowia - Suchecka, Jadwiga; Nieszporska, Sylwia (EQ-5D Questionnaires as a Methods of Indirect Measurement of Quality of Health State, 2005)
The measurements that are based on the health assessment from the patient's perspective are more often used in the nowadays study on the quality of life. Such measurements serve the assessment of equality and effectiveness in applications of different therapies, but they also become a base for economical assessment of the health care system. The main aim of this paper is the evaluation of the patients' health in one of the Czestochowa's hospitals using EQ-5D descriptive system. This system is interesting because it not only describes the health care of the respondents in a complex way, but also delivers a weighted index for health's state, which can be used in economical and clinical assessment of the health care.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 339-348